PERILAKU LEKATAN TULANGAN POLOS DAN TULANGAN ULIR PADA STRUKTUR BETON SERAT KAYU - Karimah, Rofikatul (Media Teknik Sipil, 2012)
Rofikatul KarimahFakultas Teknik Jurusan Teknik Sipil Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas 246 Malang 65144, IndonesiaKarimah@umm.ac.idABSTRACTIn addition wood powder residual sawmill.the concrete will cause a change in behaviorjuxtaposition between concrete and reinforcement steel reinforcement material either plain orreinforcement thread.The research this studyFiber is used sawmill waste wood fiber with content0%, 0.5%, 1% and 1.5% of the volume of concrete as a comparison is also made of concretewithout fibers.Specimens used were silinder30 cm x 15 cm were 12 specimens for compressive strengthtesting and 24 specimens for testing strong adhesion. By using reinforcement thread diameter D10mm and 10 mm reinforcment glace.From the research of the study isstudy iscompressive strengthwith a mixture of sawdustdeclineswith the powder in each variation the capability of strong stickbetween reinforcing steel and concreteplain wood fiber and strong adhesion between reinforcment glace stee land concrete screw woodfiber show that the strong ability adhesion reinforcment thread more thanreinforcment glace.Whilemore of fibers in the concrete mix variation, the lower the magnitude of the strong adhesion betweenthe concrete and reinforcement plain tacky.Keywords : Concrete, sawdust, compressive strength ,strong adhesive